2021
DOI: 10.1007/s11356-021-14201-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of residential greenness with hypertension and blood pressure in a Chinese rural population: a cross-sectional study

Abstract: Background: Limited epidemiological literature identi ed the associations between residential greenness and hypertension in low/middle-income countries.Methods: A random sampling strategy was adopted to recruit 39 259 residents, ≥ 18 years, and from 5 counties in central China. Blood pressure was measured based on the protocol of the American Heart Association. Hypertension was de ned according to the 2010 Chinese guidelines for the management of hypertension. The satellite-derived Normalized Difference Vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…One of the most widely discussed mediators was air pollutants, including particulate matters, NO 2 , etc. Similar to previous studies ( Jiang et al, 2021 , Yang et al, 2021 ), we also found that PM 2.5 , PM 10, and NO 2 mediated the association between greenness and COVID-19 severity, particularly to NO 2 . Studies ( Sepehri et al, 2020 , Sepehri and Sarrafzadeh, 2019 ) suggested that this compound occurs in the aqueous media.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…One of the most widely discussed mediators was air pollutants, including particulate matters, NO 2 , etc. Similar to previous studies ( Jiang et al, 2021 , Yang et al, 2021 ), we also found that PM 2.5 , PM 10, and NO 2 mediated the association between greenness and COVID-19 severity, particularly to NO 2 . Studies ( Sepehri et al, 2020 , Sepehri and Sarrafzadeh, 2019 ) suggested that this compound occurs in the aqueous media.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies ( Jiang et al, 2021 , Peng et al, 2021 , Xie et al, 2021 , Yang et al, 2021 ) conducting the association of greenness with health outcomes had attempted to uncover the potential mechanism through mediation analysis. One of the most widely discussed mediators was air pollutants, including particulate matters, NO 2 , etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a longitudinal cohort study on the association between residential greenness and mortality reported a stronger association in never smokers (HR: 1.09, 95% CI 1.04–1.14) than in smokers (HR: 1.03, 0.91–1.17) [ 34 ]. In contrast, smokers benefitted more from the effects of greenness than never smokers with decreased blood pressure [ 35 ] and the prevalence of chronic kidney disease [ 36 ]. Therefore, both smokers and never-smokers can benefit from exposure to residential greenness.…”
Section: Discussionmentioning
confidence: 99%
“…Greenness usually comprises vegetation and is closely associated with natural elements [ 1 ]; it is a widely used environmental indicator in the medical and health sciences field. An increasing number of studies have confirmed that greenness is beneficial for cardiovascular health [ 2 , 3 ]. Greenness can offset the effects of environmental hazards and reduce damage to the cardio-cerebral vascular system caused by air pollutants, heat, and noise; greenness exposure can relieve mental stress as well as help reduce the proportion of overweight and obese individuals [ 4 ].…”
Section: Introductionmentioning
confidence: 99%